Influence of Pre-pregnancy and During Pregnancy Exercise On Infant Heart Outcomes - Langford, Benjamin (East Carolina University, 2017)
Maternal exercise during pregnancy is quickly becoming a new norm that has been shown to have benefits for fetal and infant development. Most studies examining the influence of exercise during pregnancy on infant outcomes have utilized women that were previously active and the exercise was self-reported. We do not know if similar changes in infant HR and HRV occur from an exercise intervention in women that were sedentary prior to pregnancy. This study will address this gap. The purpose of this study is to determine if exercise during pregnancy is the main influence of one-month-old infant heart rate (HR) and HR variability (HRV), regardless of physical activity habits before pregnancy. We hypothesized that exercise during pregnancy is the most significant predictor of lower infant heart rate and increased heart rate variability, regardless of exercise prior to pregnancy. Participants performed a minimum of 150 minutes of moderate intensity aerobic activity (40-59% heart rate reserve [HRR]) through three 50 minute sessions per week starting at 16 weeks gestational age (GA) through birth. Controls were received no exercise intervention. Participants completed an activity questionnaire to determine activity level prior to pregnancy. Heart rate (HR) and heart rate variability (HRV) were recorded in infants one-month after birth. Measures of HRV included for analysis were SDNN, RMSSD, Total Power, VLF, LF, HF, and LF:HF ratio, which are representative of improved sympathetic, parasympathetic, and overall autonomic development. Participants were analyzed using t-tests between active and inactive women before pregnancy, active and inactive women during pregnancy as well as using multiple ANOVAs between 4 groups: Active: Active (AA), Active: Inactive (AI), Inactive: Active (IA), and Inactive: Inactive (II). Statistical analyses also included correlations and multiple regression analyses. Participants (n=21) were similar in age, body mass index (BMI), and parity. There were 15 male and 6 female infants born. Infants of participants who were active during pregnancy had significantly lower average HR, and higher measures of SDNN and RMSSD (p=.02; p=.01, p=.02), respectively. Infants of participants whose mothers were inactive before pregnancy and active during pregnancy (IA) had lowest average heart rate of the four groups. Based on the updated exercise guidelines adopted by the American College of Sports Medicine (ACSM) from the American Congress of Obstetrics and Gynecology (ACOG), the results of this present study suggest that 1) Increased physical activity levels in women during pregnancy is associated with lower infant heart rates and higher markers of heart rate variability in comparison to those who did not exercise during pregnancy. 2) Participating in exercise during pregnancy when previously inactive can potentially yield greater benefit than just activity before pregnancy. 3) Increasing physical activity during pregnancy is correlated with lower infant heart rates and higher measures of heart rate variability. Our results provide support to continue or to begin a moderate intensity aerobic exercise program in low-risk pregnancies. Further research is needed, but this supports the notion that exercise during pregnancy may be one of the earliest interventions to improve infant heart health and decrease risk of heart disease.
Keywords: Exercise for pregnant women; Pregnant women--Health and hygiene; Prenatal care